Stakeholder perspectives on the stigma of fetal alcohol spectrum disorder. (4th March 2019) - Corrigan, Patrick W.; Shah, Binoy Biren; Lara, Juana Lorena; Mitchell, Kathleen T.; Combs-Way, Peggy; Simmes, Diana; Jones, Kenneth L.
Abstract: Background: Fetal Alcohol Spectrum Disorder (FASD) is a condition afflicting children born to women who consumed alcohol during pregnancy that can lead to secondary disabilities including cognitive and social deficits. Both, children with FASD, and their biological mothers, are targets of FASD stigma. This study seeks to identify stereotypes, prejudice, and discrimination corresponding to FASD stigma. Methods: Nine stakeholders comprised a community based participatory research (CBPR) team to discuss logistics, identify focus groups, and develop a qualitative interview guide. Attitudes and beliefs regarding children with FASD and their biological mothers were obtained from four focus groups of people: adults with FASD, biological mothers, other relatives, and health care providers. In addition, three one-on-one interviews were completed. Responses were coded into themes by two independent raters. Results: Analyses yielded themes that distinguished between stigmatizing perceptions of children with FASD (e.g., immature, lazy, violent, socially inept) and biological mothers (e.g. child abusers, in denial, secretive, ignorant). Discrimination perpetuated by health care providers undermined services received by biological mothers and their children with FASD (e.g., lack of understanding, lack of identification, poor communication skills). Lastly, discriminatory behaviors specific to children with FASD and their biological mothers were identified (e.g., neglect, avoidance, abuse). Conclusion: Results described the stigma experienced by different stakeholders related to FASD by identifying specific candidates for stereotypes, prejudice, and discrimination. These findings can be used to inform further assessment of stigma and also the development of tailored anti-stigma interventions.